"pz-qz=z^2+(x+y)^2\\\\\n\\frac{dx}{z}=\\frac{dy}{-z}=\\frac{dz}{z^2+(x+y)^2}\\\\\n1) \\frac{dx}{z}=\\frac{dy}{-z}\\implies\\\\\n-dx=dy\\implies -\\int dx=\\int dy\\implies\\\\\n-x+c_1=y \\implies c_1=x+y\\\\\n2) \\frac{dx}{z}=\\frac{dz}{z^2+(x+y)^2}\n\\implies\\\\\n\\frac{dx}{z}=\\frac{dz}{z^2+c_1^2}\\implies\\\\\ndx=\\frac{zdz}{z^2+c_1^2} \\implies\\\\\n\\int dx=\\int\\frac{zdz}{z^2+c_1^2}\\implies\\\\\n\\int dx=\\frac{1}{2}\\int\\frac{d(z^2+c_1^2)}{z^2+c_1^2}\\implies\\\\\n\\frac{1}{2}\\ln|z^2+c_1^2|=x+\\frac{1}{2}\\ln|c_2|\\implies\\\\\n\\ln|z^2+c_1^2|=2x+\\ln|c_2|\\implies\\\\\nz^2+c_1^2=c_2e^{2x}\\implies\\\\\nz^2+(x+y)^2=c_2e^{2x}\\implies\\\\\nc_2=\\frac{z^2+(x+y)^2}{e^{2x}}\\\\"
Solution of equation is
"F(x+y, \\frac{z^2+(x+y)^2}{e^{2x}})=0"
Comments
Leave a comment